Text-fig. 8. a–e: Quercus aff. cerris. a: Cup, Oriolo MSF 984. b: Cup, Oriolo MSF 982. c: Leaf, Oriolo MSF 689. d: Leaf, Oriolo MSF 659. e: Oriolo MSF 657. f: Quercus aff. pubescens Oriolo MSF 688. g: Quercus sect. Quercus acorn, Oriolo MSF 658. h–j: Quercus iberica. h: Oriolo MSF 694. i: Oriolo MSF 639. j: Oriolo MSF 698. Scale bars 10 mm (a, b, g), 50 mm (c–f, h–j). in The Late Early Pleistocene Flora Of Oriolo, Faenza (Italy): Assembly Of The Modern Forest Biome - Denk, Thomas; Sami, Marco; Teodoridis, Vasilis; Martinetto, Edoardo (Zenodo, 2022)
Text-fig. 8. a–e: Quercus aff. cerris. a: Cup, Oriolo MSF 984. b: Cup, Oriolo MSF 982. c: Leaf, Oriolo MSF 689. d: Leaf, Oriolo MSF 659. e: Oriolo MSF 657. f: Quercus aff. pubescens Oriolo MSF 688. g: Quercus sect. Quercus acorn, Oriolo MSF 658. h–j: Quercus iberica. h: Oriolo MSF 694. i: Oriolo MSF 639. j: Oriolo MSF 698. Scale bars 10 mm (a, b, g), 50 mm (c–f, h–j). Published as part of Denk, Thomas, Sami, Marco, Teodoridis, Vasilis & Martinetto, Edoardo, 2022, The Late Early Pleistocene Flora Of Oriolo, Faenza (Italy): Assembly Of The Modern Forest Biome, pp. 217-262 in Fossil Imprint 78 (1) on page 233, DOI:10.37520/fi.2022.009, http://zenodo.org/record/7167867